SEKULARISASI DAN ISLAMISASI ILMU PENGETAHUAN - Saude, Saude (Institut Agama Islam Negeri (IAIN) Palu, 2008)
Discourse on islamization of knowledge essentially emerges from the serious concern to the failure of modern sciences to âgive welfare to humanityâ. The basic problem is rooted in the philosophical framework behind modern sciences that science is free-value in that science is purely for science itself regardless of its impacts to humanity and environment. This in turn paves a way to sciences to go further without any impediment, or even without any purpose except for science itself. As a result, nature and humanity are exploited on behalf of science. Therefore, it is necessary to restore science into its proper position. Islam as a religion, which gives serious concern to knowledge and science, has views of knowledge and sciences which are different from a secular concept of science. This paper will discuss this issue.Kata Kunci : sekularisasi, islamisasi ilmu pengetahuan